Heavy Minerals contents in Sandstone beds from Tanjero Formation (late Campanian - Maastrichtian) in Sulaimaniyah governorate northeast of Iraq - kareem hussien Khwedim; Zubaida Asem (Academic Science Journal)
Tanjero Formation (late Campanian – Maastrichtian) mainly occurs in the balambo-tanjero zone, it also occurs in the high folded zone. Twenty sandstone samples were collected from two section of Tanjero Formation (Dokan and Qamchuqa) from Sulaimaniyah governorate northeast of Iraq.  The obtained data indicates that the most abundant heavy minerals are opaque, followed by  pyroxene ,chlorite, amphibole, epidote, garnet ,mica ,Staurolite , tourmaline and rutile. According to heavy minerals assemblage, the source rocks are interpreted to be composed essentially of sedimentary followed by acidic and basic igneous and metamorphic rocks and the high contents of unstable and stable  minerals confirm their direct derivation from the adjacent primary source. the relationship between an ultra-stable and a meta-stable heavy mineral indicated the immaturity of the Tanjero Formation sandstone and its moderate stability, proving that these minerals cannot be transported over extremely long distances close to the source rocks area. The heavy mineral assemblage demonstrated that the studied area is distinguished by high tectonic activity. In addition, according to the MF- MT-GM ternary diagram, the analyzed sandstone samples lie within the active continental margins field, which is distinguished by a higher percentage of MF minerals than GM minerals generated from mafic magmatic source rocks.